PERJUANGAN MULTIKULTURALISME PERHIMPUNAN INDONESIA TIONGHOA DALAM PERSPEKTIF REKOGNISI AXEL HONNETH - Marta, Rustono Farady (Universitas Bunda Mulia, 2018)
Social equality among human beings is the ideal condition that has been initiated byphilosophers such as Hegel and Mead, but Axel Honneth offers a different perspective on bothimplementation levels and a more holistic perspective. One of the thoughts related to the acquisition ofHonneth's recognition through his postulate, has illustrated that there is a struggle on the basis ofawareness of respect and recognition of cultural identity in the realm of multiculturalism. In the strugglethere are several steps that must be passed to obtain mutual recognition of the particular identity, wherethe working principle starts from the affective level of love, then the cognitive is in the realm of the legalorder, until the intellectual intuition is poured in the form of solidarity. These three become forms ofreciprocal relationships that lead to the acquisition of recognition in several stages in every phase ofsociety's development. This is in line with the struggle of the Chinese Association of China (INTI) which isalways at the forefront of diffusing the implementation of multiculturalism to the wider community.Recognition of the equal rights and obligations of citizens is an essential human role, as well as the ethnicChinese Indonesian community that has become an integral and fundamental part of the Unitary State ofthe Republic of Indonesia (NKRI). Unfortunately, past political policies 'scratch' history track record thatactually creates a negative perception related to the existence of this ethnic.Keywords: Axel Honneth Recognition, Multiculturalism, Perhimpunan INTI